Dynamics of hardiness personality on Indonesian muslim online celebrities - Henie Kurniawati; Oki Edi Purwoko; Shaula Astika Putri (Jurnal Konseling dan Pendidikan, 2023)
Celebrities are figures who actively share entertainment content in society with a large number of followers and they are popular or well-known known to many people. The main objective of this research is to determine the dynamics of hardiness personality on Indonesian Muslim online celebrities. This research uses a qualitative approach, the subjects work as celebrities/have an active Indonesian Instagram and YouTube accounts, have a minimum of 1000 followers, live in Indonesia, have been in the entertainment sector for at least 1 year. The interview method is using CRQ-TQ-IQ-II algorithmic model, which are consisted of: Central Research Question, Theory Question, Interview Question, and Interview Intervention. Research conclusions, The hardiness personality evolves, fostering a desire for visibility, creativity, attractiveness, and celebrity-like active behavior. Supporting factors in Muslim celebrities include a wish for visibility, widespread recognition demonstrated through various means, fueled by pride and joy in entertaining and benefiting others. Inhibiting factors, like exclusion, fear of rejection, sensitivity to criticism, challenges, condemnation, or negative social media comments, minimally affect their personality growth, showcasing their adeptness at navigating and evolving in line with individual dynamics.